Optimal. Leaf size=25 \[ e^{-5+e^{\frac {e^{-2 x}}{3}}}-e^{(-5+x)^2} \]
________________________________________________________________________________________
Rubi [A] time = 0.32, antiderivative size = 25, normalized size of antiderivative = 1.00, number of steps used = 9, number of rules used = 6, integrand size = 53, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.113, Rules used = {12, 6742, 2282, 2194, 2227, 2209} \begin {gather*} e^{e^{\frac {e^{-2 x}}{3}}-5}-e^{(x-5)^2} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 2194
Rule 2209
Rule 2227
Rule 2282
Rule 6742
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {1}{3} \int e^{-2 x} \left (-2 e^{-5+e^{\frac {e^{-2 x}}{3}}+\frac {e^{-2 x}}{3}}+3 e^{25-8 x+x^2} (10-2 x)\right ) \, dx\\ &=\frac {1}{3} \int \left (-2 e^{-5+e^{\frac {e^{-2 x}}{3}}+\frac {e^{-2 x}}{3}-2 x}-6 e^{25-10 x+x^2} (-5+x)\right ) \, dx\\ &=-\left (\frac {2}{3} \int e^{-5+e^{\frac {e^{-2 x}}{3}}+\frac {e^{-2 x}}{3}-2 x} \, dx\right )-2 \int e^{25-10 x+x^2} (-5+x) \, dx\\ &=\frac {1}{3} \operatorname {Subst}\left (\int e^{\frac {1}{3} \left (-15+3 e^{x/3}+x\right )} \, dx,x,e^{-2 x}\right )-2 \int e^{(-5+x)^2} (-5+x) \, dx\\ &=-e^{(-5+x)^2}+\operatorname {Subst}\left (\int e^{-5+e^x+x} \, dx,x,\frac {e^{-2 x}}{3}\right )\\ &=-e^{(-5+x)^2}+\operatorname {Subst}\left (\int e^{-5+x} \, dx,x,e^{\frac {e^{-2 x}}{3}}\right )\\ &=e^{-5+e^{\frac {e^{-2 x}}{3}}}-e^{(-5+x)^2}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.16, size = 25, normalized size = 1.00 \begin {gather*} e^{-5+e^{\frac {e^{-2 x}}{3}}}-e^{(-5+x)^2} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [B] time = 0.56, size = 57, normalized size = 2.28 \begin {gather*} -{\left (e^{\left (x^{2} - 10 \, x + e^{\left (-2 \, x - \log \relax (3)\right )} + 25\right )} - e^{\left (e^{\left (-2 \, x - \log \relax (3)\right )} + e^{\left (e^{\left (-2 \, x - \log \relax (3)\right )}\right )} - 5\right )}\right )} e^{\left (-e^{\left (-2 \, x - \log \relax (3)\right )}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} \int -2 \, {\left ({\left (x - 5\right )} e^{\left (x^{2} - 8 \, x + \log \relax (3) + 25\right )} + e^{\left (e^{\left (-2 \, x - \log \relax (3)\right )} + e^{\left (e^{\left (-2 \, x - \log \relax (3)\right )}\right )} - 5\right )}\right )} e^{\left (-2 \, x - \log \relax (3)\right )}\,{d x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.04, size = 20, normalized size = 0.80
method | result | size |
risch | \(-{\mathrm e}^{\left (x -5\right )^{2}}+{\mathrm e}^{{\mathrm e}^{\frac {{\mathrm e}^{-2 x}}{3}}-5}\) | \(20\) |
default | \(-{\mathrm e}^{x^{2}-10 x +25}+{\mathrm e}^{{\mathrm e}^{\frac {{\mathrm e}^{-2 x}}{3}}} {\mathrm e}^{-5}\) | \(24\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [C] time = 0.44, size = 59, normalized size = 2.36 \begin {gather*} -\frac {5 \, \sqrt {\pi } {\left (x - 5\right )} {\left (\operatorname {erf}\left (\sqrt {-{\left (x - 5\right )}^{2}}\right ) - 1\right )}}{\sqrt {-{\left (x - 5\right )}^{2}}} - 5 i \, \sqrt {\pi } \operatorname {erf}\left (i \, x - 5 i\right ) - e^{\left ({\left (x - 5\right )}^{2}\right )} + e^{\left (e^{\left (\frac {1}{3} \, e^{\left (-2 \, x\right )}\right )} - 5\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 4.27, size = 24, normalized size = 0.96 \begin {gather*} {\mathrm {e}}^{-5}\,{\mathrm {e}}^{{\left ({\mathrm {e}}^{{\mathrm {e}}^{-2\,x}}\right )}^{1/3}}-{\mathrm {e}}^{-10\,x}\,{\mathrm {e}}^{x^2}\,{\mathrm {e}}^{25} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.45, size = 22, normalized size = 0.88 \begin {gather*} e^{e^{\frac {e^{- 2 x}}{3}} - 5} - e^{x^{2} - 10 x + 25} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________